2012
DOI: 10.1038/jp.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia during neonatal transport: data from the California Perinatal Quality Care Collaborative (CPQCC) and California Perinatal Transport System (CPeTS) for 2010

Abstract: More than half of the infants cooled in transport do not achieve target temperature by the time of arrival at the cooling center. The use of cooling devices may improve temperature regulation on transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…As such, the CPQCC has proven to be a valuable tool to audit and improve care of preterm babies in California and provides a broad and rich data set to inform medical and parental decision making for these high-risk infants. [3][4][5][6] The current study was a retrospective database review of births o 32 weeks gestation and o 1500 g birth weight reported to the CPQCC between 2005 and 2012. Profoundly SGA (ProSGA, birth weight o 1st centile for age) and profoundly low birth weight (ProLBW, birth weight 300 to 500 g) subjects were identified, and comparisons were made between the ProSGA infants and appropriate for gestational age infants (AGA, 5 th to 95th weight centile at birth) and between ProLBW and very low birth weight (VLBW) infants (birth weight 501 to 1500 g).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the CPQCC has proven to be a valuable tool to audit and improve care of preterm babies in California and provides a broad and rich data set to inform medical and parental decision making for these high-risk infants. [3][4][5][6] The current study was a retrospective database review of births o 32 weeks gestation and o 1500 g birth weight reported to the CPQCC between 2005 and 2012. Profoundly SGA (ProSGA, birth weight o 1st centile for age) and profoundly low birth weight (ProLBW, birth weight 300 to 500 g) subjects were identified, and comparisons were made between the ProSGA infants and appropriate for gestational age infants (AGA, 5 th to 95th weight centile at birth) and between ProLBW and very low birth weight (VLBW) infants (birth weight 501 to 1500 g).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The data provided by Akula et al 2 extends prior publications by adding a larger data set extracted from a database with systematic collection of admission temperatures from multiple transport teams and NICUs. Initiation of therapeutic hypothermia at referring hospitals and on transport is a logical means to extend an effective therapy to more infants who are at risk for mortality or serious morbidity following hypoxia-ischemia.…”
mentioning
confidence: 92%
“…The report by Akula et al 2 in this issue of the Journal of Perinatology provides important data regarding therapeutic hypothermia during neonatal transport. Two databases in California were used to examine transport practices and temperatures upon admission to centers providing therapeutic hypothermia and represents data from 490% of newborns requiring NICU care in the state during 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If, after ≥1 h of cooling, core rectal temperature remains >35.5°C, refrigerated gel packs are applied. Referral hospital initiation of hypothermia aims to achieve the target temperature as soon as possible [17], an approach also used by other transport services [5,6,18] but differing to the ICE trial, in which only the transport team (or tertiary NICU) initiated cooling. It is recognised that uncontrolled cooling at referring hospitals may increase the risk of overcooling to <33°C, reported in 11-44% of outborn infants with HIE treated with hypothermia [5,7,18,19,20].…”
Section: Methodsmentioning
confidence: 99%